2021
DOI: 10.1158/1541-7786.mcr-21-0014
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of m6A and Its Regulatory Targets in Prostate Cancer Reveals a METTL3-Low Induction of Therapy Resistance

Abstract: Recent evidence has highlighted the role of N 6 -methyladenosine (m 6 A) in the regulation of mRNA expression, stability and translation, supporting a potential role for posttranscriptional regulation mediated by m 6 A in cancer. Here we explore prostate cancer as an exemplar and demonstrate that low levels of N 6 -adenosine-methyltransferase (METTL3) is associated with advanced metastatic disease. To investigate this relationship, we generated the first prostate m 6 A maps, and further examined how METTL3 reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 74 publications
(104 reference statements)
4
35
0
Order By: Relevance
“…This concept has been recently validated in murine cancer models ( 78 ). Fifth, a negative correlation of AR activity with m 6 A activity is noticed, and together with a recent report that AR is not a direct target of METTL3 ( 79 ), we propose AR and m 6 A axis as independent contributors in driving PCa progression. Sixth, m 6 Avalue, a weighted score established from 87 key m 6 A-associated genes, well separates indolent pri-PCa from aggressive ones, with the m 6 Avalue high group being more stem-like, proliferative and nonfibrotic.…”
Section: Discussionsupporting
confidence: 81%
“…This concept has been recently validated in murine cancer models ( 78 ). Fifth, a negative correlation of AR activity with m 6 A activity is noticed, and together with a recent report that AR is not a direct target of METTL3 ( 79 ), we propose AR and m 6 A axis as independent contributors in driving PCa progression. Sixth, m 6 Avalue, a weighted score established from 87 key m 6 A-associated genes, well separates indolent pri-PCa from aggressive ones, with the m 6 Avalue high group being more stem-like, proliferative and nonfibrotic.…”
Section: Discussionsupporting
confidence: 81%
“…YTHDF2, a reader of m6A modification, synergistically induces PCa progression with METTL3 by regulating AKT phosphorylation [ 15 ]. However, low levels of METTL3 were also found to lead to advanced metastatic PCa that is resistant to androgen receptor antagonists [ 35 ]. These controversial results reveal the complexity of m6A regulators and individual heterogeneity of m6A regulators in PCa, and various m6A regulators may form a complex network structure and interact with each other to affect PCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, GO analysis showed that ELAVL1-immunoprecipitated mRNAs were associated with RNA metabolism functions, including RNA decay, translation, splicing, and nuclear export ( Figure 5D ). Previous studies have shown that PCa development is associated with RNA metabolism due to m6A imbalance ( 49 51 ). Therefore, we speculate that ELAVL1 in PCa may be involved in tumor development by regulating the RNA metabolism of m6A regulators.…”
Section: Resultsmentioning
confidence: 99%